Appropriate level of development of in-situ building information modeling for existing building energy modeling implementation. (15th June 2023) - Jung, Dong Eun; Kim, Seohoon; Han, Seolyee; Yoo, Seunghwan; Jeong, Hakgeun; Lee, Kwang Ho; Kim, Jonghun
Abstract: Existing buildings deteriorate over time, and the energy consumption continues to increase. In order to improve energy efficiency, evaluation of the energy performance of the existing buildings through simulation is required in advance. However, for most existing buildings, drawing information for evaluating energy performance is omitted. Without drawing information, the building energy cannot be modeled and energy cannot be predicted. To solve this problem, the building information modeling (BIM)-building energy modeling (BEM) process based on 3D laser scanning has recently been attracting considerable attention. When there is no drawing information in this process, geometric information of the existing building can be implemented through BIM. In addition, it is extremely important to determine the level of development (LOD) of the BIM because the accuracy of energy prediction depends on the LOD. In other words, the LOD of in-situ BIM should be determined for accurate building energy performance evaluation. Therefore, this study proposes an appropriate LOD of in-situ BIM for BEM implementation of existing buildings. Accordingly, the BIM-BEM process was applied and the building energy performance was evaluated. In addition, the uncertainty and accuracy were analyzed through comparison with the measured building energy consumptions. As a result of the analysis, LOD 350 was determined as a suitable LOD, capable of simulating the energy performance of an actual building. Highlights: Appropriate LOD of in-situ BIM proposed for BEM implementation of existing buildings. Uncertainty and accuracy analyzed for LOD 200, 300, and 350. LOD 350 is closest to the ASHRAE Guideline 14 (CvRMSE<15%, NMBE<±5%). Impact of variables on building energy consumption of BEM is significant.